Has COVID-19 changed the approach to HIV diagnosis?: A multicentric Italian experience. Issue 41 (15th October 2021) - Mazzitelli, Maria; Ciccullo, Arturo; Baldin, Gianmaria; Cauda, Roberto; Rusconi, Stefano; Giacomelli, Andrea; Oreni, Letizia; Borghi, Vanni; Mussini, Cristina; Guaraldi, Giovanni; Sterrantino, Gaetana; Lagi, Filippo; et al.
Abstract : Abstract: The occurrence of COVID-19 pandemic had a significant negative effect on health care systems over the last year. Health care providers were forced to focus mainly on COVID-19 patients, neglecting in many cases equally important diseases, both acute and chronic. Therefore, also screening and diagnostic strategies for HIV could have been significantly impaired. This retrospective, multicenter, observational study aimed at assessing the number and characteristics of new HIV/AIDS diagnoses during COVID-19 pandemic in Italy and compared characteristics of people living with HIV at diagnosis between pre- and post-COVID-19 era (2019 vs 2020). Our results showed a significant reduction of HIV diagnoses during pandemic. By contrast, people living with HIV during pandemic were older and were diagnosed in earlier stage of disease (considering CD4+ T cell count) compared to those who were diagnosed the year before. Moreover, there was a significant decrease of new HIV diagnoses among men who have sex with men, probably for the impact of social distancing and restriction applied by the Italian Government. Late presentation incidence, if numbers in 2020 were lower than those in 2019, is still an issue. Routinely performing HIV testing in patients with suspected SARS-CoV-2 infection is identifying and linking to care underdiagnosed people living with HIV earlier. Thus, combined tests (HIV and SARS-CoV-2) should be implemented in patients with SARS-CoV-2 symptoms overlapping HIV's ones. Lastly, our results lastly showed how urgent implementation of a national policy for HIV screening is necessary.